Design of a Community Manager System for a Multiagent Web Operating System (Publicaciones en Ciencias y Tecnología, 2008)
This paper describes the design of a Community Manager System for a Multiagent Web Operating System. The system allows virtual gathering of nodes in communities, according to specific criteria, with the objective of improving the efficiency and performance of the Multiagent Web Operating System. The design is made and verified according to MASINA, a methodology for agent specification.
Keywords: Multiagent Systems; Web Operating Systems; Self-Organization; Virtual Communities